If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -4 = (x + 1) Reorder the terms: -4 + 2x = (x + 1) Reorder the terms: -4 + 2x = (1 + x) Remove parenthesis around (1 + x) -4 + 2x = 1 + x Solving -4 + 2x = 1 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -4 + 2x + -1x = 1 + x + -1x Combine like terms: 2x + -1x = 1x -4 + 1x = 1 + x + -1x Combine like terms: x + -1x = 0 -4 + 1x = 1 + 0 -4 + 1x = 1 Add '4' to each side of the equation. -4 + 4 + 1x = 1 + 4 Combine like terms: -4 + 4 = 0 0 + 1x = 1 + 4 1x = 1 + 4 Combine like terms: 1 + 4 = 5 1x = 5 Divide each side by '1'. x = 5 Simplifying x = 5
| -1-r=8(r-8) | | sqrt(tanx)dx=0 | | 2x^4-7x^3+3x^2=0 | | 5x-7x=2+3x | | 3(y-8)/5=-4y | | y+30=15 | | -5(x-7)=35+6x | | -3(x-4)-8x=3x-3 | | -4(7+3n)+3=-85 | | 0.75+0.12t=2.57t-0.23 | | f(x)=5x^2+2x-10 | | 5a+17=12 | | 9/7n=30 | | 7/5x=21 | | .13-01(x+1)=-.03(4-x) | | 2(6-6x)+7(x-7)=Ax+B | | 14/3+1/5t=7 | | 3(5x+6)=-12+15 | | 0=x^2-14x+24 | | 6u^3(-2u^5)= | | 0=8h^2+12h-4896 | | y=2x^2-x+2 | | 3x(x-9)=13x^2-28x | | 1=15t-5t^2 | | 3.6q-1.2-4.1q=-1.5q-5.1 | | (x^2+12x)+(3x^2+20)=180 | | 6w=3P-6l | | 9xsquared+4=12x | | 0=x^2-12x+11 | | 8(t-4)+4t=4(3t+3)-9 | | 7h+2h-5=19 | | 8x-4=5x+1 |